Qualitative study of women's experience after therapeutic massage - Garakyaraghi, Mohammad (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Hypertension has become a major problem throughout the world, especially in developing countries like Iran. As it is a major risk factor for coronary heart disease, even small reductions in the prevalence can have potentially large public health benefits. Among the complementary methods, massage provides an effective means to lower the blood pressure. If nurses perceive the experiences of hypertensive patients receiving massage, they can use massage more effectively in their care plan. MATERIALS AND METHODS: This is a descriptive phenomenological study. Deep interviews were conducted with nine prehypertensive women who received Swedish massage three times a week in a total of 10 sessions, with each session lasting 10-15 min. Then, the researcher conducted an interview using a ‘grand tour question (open ended question) and the participants were then encouraged to speak freely explaining their thoughts and feelings about the experience of massage therapy. Data analysis was done by Colaizzi's method. Validity and reliability were obtained through measures such as real value, applicability, continuity, and authenticity. RESULTS: Women evaluated the massage therapy positively. The findings yielded six themes, including relaxation, sleeping better, reduction of anxiety and tension, reduction of fatigue, invigorating experience, improve connecting. CONCLUSIONS: This study demonstrates that a body-centered intervention like massage can be valuable in a multidisciplinary approach to women with prehypertension. This method is easy to learn and relatively short (10-15 min) to administer as a suitable complement in nursing care for this group of patients.